Revitalizing Nerves: Panchakarma Therapy for Diabetic Neuropathy (AYUSHDHARA, 2024)
Diabetic Peripheral Neuropathy (DPN) is one of the most common and debilitating complications of diabetes, affecting the peripheral nervous system resulting from prolonged elevated blood sugar levels. In Ayurveda, diabetes mellitus closely resembles a disorder called Madhumeha. In Avaranajanya Madhumeha- vitiated Kapha, Pitta and Meda causes Avarana to Vata that affects the vital Dhatus. This may lead to the complication of Madhumeha as that of diabetic neuropathy. A 44-year-old female patient diagnosed with type 2 diabetes mellitus and exhibiting symptoms of DPN-such as numbness, reduced sensation and weakness in the extremities- treated with a combination of Ayurvedic oral medication and external therapies. Considering the treatment protocol of Prameha upadrava and Vatavyadhi chikitsa, internally, Ksheerabala 101 Capsule, and Avipattikara churna were used during the course of treatment. External therapies including Udwartana, Abhyanga and Masha upanaha were done for a duration of 14 days. Ayurveda's integrative approach addresses both the root cause and symptoms of DPN, offering a natural and sustainable alternative for managing diabetic complications. This outcome emphasizes the potential efficacy of combining traditional Ayurvedic treatments with conventional care in the management of diabetic peripheral neuropathy.